Intercultural Communicative Competence Levels of Indonesian EFL Students: A Preliminary Study in a Higher Education Context - Anna Riana Suryanti Tambunan; Fauziah Khairani Lubis; Widya Andayani; Winda Setia Sari (Institut Agama Islam Negeri (IAIN) Kendari, 2021)
The lack of intercultural communication skills will likely cause disharmony, misunderstanding, and even conflict in communication. To be successful in communication with native speakers depends on language skills, customs, and cultural knowledge. In the age of global communication, English as a Foreign Language (EFL) teaching goals should be reoriented to cultivate intercultural communication competence (ICC). EFL learners should have this intercultural competence and be sensitive in order to avoid disharmony, misunderstandings, and even conflicts in communication. The main objective of this preliminary study is to reveal the levels of intercultural communicative competence among EFL students at a state university in Indonesia. A survey questionnaire was performed employing a quantitative analysis in this study. Eighty-nine students filled out the ICC questionnaire, which consisted of 20 questions. Findings indicated that most of the students had a low ICC level because they are lack of experience and knowledge in interacting and socializing with people from various cultural backgrounds. In terms of gender differences, the results showed that male students had higher levels of ICC than that female students. This research implied that intercultural topics should be included in the university’s curriculum.